2012
DOI: 10.1007/s10853-012-6322-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline nickel dispersed with nano-size WO3 particles synthesized by electrodeposition

Abstract: A new class of bulk nanocrystalline nickel dispersed with nano-scale WO 3 particles has been synthesized by conventional electrodeposition to clarify the effect of the presence of nano-size dispersions on the strength and thermal stability of nanocrystalline structures. It was found that WO 3 particles of an initial size of 0.1 lm, when suspended in an electrolyte, fragmented into smaller nano-size particles, and were embedded into nanocrystalline nickel matrix of an average grain size of 45 nm during depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The catalysts WO 3 /CNT‐1 and WO 3 /CNT‐2 improved by [C 16 mim]Cl had strong characteristic diffraction peaks at 2 θ = 22.95, 23.82, 28.58, 33.29 and 34.03°, indexed as the (0 0 1), (2 0 0), (2 1 0), (2 0 1) and (2 2 0) reflections of tetragonal phase WO 3 (PDF No. 89‐1287) respectively . However, in the absence of [C 16 mim]Cl, the calcined catalysts showed characteristic peaks of monoclinic phase WO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalysts WO 3 /CNT‐1 and WO 3 /CNT‐2 improved by [C 16 mim]Cl had strong characteristic diffraction peaks at 2 θ = 22.95, 23.82, 28.58, 33.29 and 34.03°, indexed as the (0 0 1), (2 0 0), (2 1 0), (2 0 1) and (2 2 0) reflections of tetragonal phase WO 3 (PDF No. 89‐1287) respectively . However, in the absence of [C 16 mim]Cl, the calcined catalysts showed characteristic peaks of monoclinic phase WO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…89-1287) respectively. 28 However, in the absence of [C 16 mim]Cl, the calcined catalysts showed characteristic peaks of monoclinic phase WO 3 . This indicated that the addition of [C 16 mim]Cl would transform monoclinic phase WO 3 on CNT into tetragonal phase WO 3 .…”
Section: Characterization Of Catalysts Xrd Analysismentioning
confidence: 99%
“…During electrodeposition, it is possible that the plate of the surface rises above this temperature locally by the discharge of electricity. In our previous study [22,23], original WO 3 particles suspended in the electrolyte were monoclinic, but were identified as tetragonal structures in the electrodeposits by XRD and TEM.…”
Section: Characterizationmentioning
confidence: 93%
“…In view of a possible change in the dominant deformation mechanism from conventional dislocation slip to deformation mediated by grain boundaries, additional hardening by WO 3 particles is of interest. Thus, as was performed in the previous report [22], the result was compared with the theoretical strengthening by classical dislocation-pinning. According to the Orowan dislocation bowing model [26], yield stress σOR can be described as:…”
Section: Effect Of Dispersions On Hardness Of Nanocrystalline Nimentioning
confidence: 94%
See 1 more Smart Citation